Interferometric RotoSAR. Issue 18 (1st September 2015) - Pieraccini, M.; Papi, F.; Rocchio, S.
Abstract : A synthetic aperture radar (SAR) system (RotoSAR) is proposed based on a radar head fixed at a rotating arm with antennas aimed in the direction orthogonal to the plane of rotation. This system is able to provide SAR images and the three components of displacement vectors of the targets in the field of view.